2011
DOI: 10.2147/opth.s22923
|View full text |Cite
|
Sign up to set email alerts
|

Grid photocoagulation combined with intravitreal bevacizumab for recurrent macular edema associated with retinal vein occlusion

Abstract: Purpose:To report the efficacy of grid photocoagulation combined with intravitreal bevacizumab (IVB) for macular edema recurring after previous IVBs associated with retinal vein occlusion (RVO).Methods:This retrospective study consisted of 19 eyes with branch retinal vein occlusion (BRVO) and nine eyes with central retinal vein occlusion (CRVO), which were treated with grid photocoagulation combined with IVB for recurrent macular edema after previous IVBs. The mean duration of total follow-up was 29.3 ± 5.8 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
(18 reference statements)
1
5
0
Order By: Relevance
“…This study showed that retreatment with IVB alone had a substantial effect on both reduction of CST and improvement in VA. In contrast, although the combination retreatment also had a significant effect on reducing CST, its effect on improving VA was limited, which concurs with a recently published report [ 24 ]. Although CST tended to be thicker in Group 2, the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study showed that retreatment with IVB alone had a substantial effect on both reduction of CST and improvement in VA. In contrast, although the combination retreatment also had a significant effect on reducing CST, its effect on improving VA was limited, which concurs with a recently published report [ 24 ]. Although CST tended to be thicker in Group 2, the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 90%
“…In regard to the number of IVB treatments, previous studies have shown that additional grid laser photocoagulation for recurrent ME in BRVO after IVB treatment may reduce the number of IVB treatments [ 23 , 24 ]. Because those studies were uncontrolled, were nonrandomized, and involved small case series, it is difficult to draw reliable conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF has been shown to play an important role in increased vascular permeability. [ 15 ] Clinical and experimental studies have demonstrated that IVT and IVB are nontoxic to the retina. [ 16 17 18 ] Previous studies have compared the effects of IVT and IVB for up to 8–13 months.…”
Section: Discussionmentioning
confidence: 99%
“…Non-conventional methods of drug delivery such as periocular and intravitreal injections provide localized drug delivery but are mildly invasive in nature. However, with the recent advancement in nanoparticle based drug delivery and nanoparticle based laser heating, it is possible to device a new strategy to treat ocular diseases using functionalized nanoparticlemediated laser photocoagulation procedures to achieve a targeted, localized, and an efficient treatment of diseases of the inner retina [35, 38–41]. The noble metal nanoparticles mediated laser hyperthermia procedures exhibit an increased absorption of light at a particular wavelength due to localized surface plasmon resonance (LSPR) [15, 39, 4244].…”
Section: Introductionmentioning
confidence: 99%